Identifikasi Endoparasit pada Sapi Brahman Cross (BX) di Rumah Potong Hewan (RPH) Kota Tangerang - Aminah Aminah; Rahmi Idhatul Setiani; Fitrine Ekawasti (Acta VETERINARIA Indonesiana, 2022)
Abattoir (RPH) is very necessary as a place for monitoring and surveillance of animal diseases. RPH routinely monitors and inspects animal health. Diseases in livestock due to endoparasitic infections can be economically detrimental by affecting the health of livestock. This situation resulted in a decrease in production related to the quality of the carcass produced. Parasitic diseases rarely receive attention (neglected diseases) so that it is rarely examined for endoparasitic infections. It is necessary to examine beef cattle at the Tangerang abattoir for the presence of endoparasitic infections, both blood parasites and gastrointestinal parasites. From the results of this study, it is expected to improve the quality of livestock health maintenance and supervision services. Blood and feces samples from 25 Brahman Cross cows from Tangerang City abattoir were identified for endoparasitic infections in the blood and digestive tract. The examination carried out based on the observation of parasite morphology showed 48% blood parasite infection and 72% gastrointestinal parasite including mixed infection. The endemicity of these parasites in Indonesian abattoirs must be considered to carry out early control of pathogenic endoparasitic infections.